The Impact of Financial Literacy and Financial Behavior on Investment Decision among Private Sector Employees in Tasikmalaya City - Prayoga, Widi; Purnomo, Budi Supriatono; Purnamasari, Imas (JURNAL BISNIS STRATEGI, 2025)
This study aims to determine the extent of the influence of financial literacy and financial behavior on investment decisions among private sector employees in the city of Tasikmalaya. The population in this study is 39,775, with a sample size of 400 determined using the Slovin formula. The research method used is descriptive and verificative, with purposive sampling as the technique. This study employs multiple linear regression, F-test, and t-test. The results show that both financial literacy and financial behavior have a positive and significant impact on investment decisions, both partially and simultaneously. The added value of this research lies in its ability to provide insights into how financial literacy and financial behavior influence investment decisions, particularly among private sector employees in an emerging region like Tasikmalaya. The findings emphasize the importance of financial education in shaping investment behavior, offering valuable data to improve financial literacy programs and interventions. These insights can guide efforts to enhance financial behaviors and promote more informed investment decisions, supporting better financial decision-making among employees.